Measurement and control of a residual oxide layer on TiSi2 films employed in ohmic contact structures - Collins, George J., author; Anderson, M. E., author; Shaw, Denis M., author; Lu, Z., author; Hathcock, S., author; Nikkel, P., author; Yu, Zengqi, author; IEEE, publisher (Colorado State University. Libraries, 1996)
An inadvertent oxide layer is formed on a titanium disilicide (TiSi2) film following various wet and dry processes in a manufacturing environment. The use of H2SO4:H2O2:H2O (1:1:5) as a wet etch for excess Ti metal, prior to the high temperature anneal used to form a subsequent TiSi2 layer, is identified as the source of the undesired oxide via multiwavelength spectroscopic ellipsometry and Auger electron spectrometry studies. This inadvertent oxide layer on TiSi2 is shown to form bad electrical contacts and is a contributing source to large standby currents in polysilicon gate shunts. Spectroscopic ellipsometry is shown herein as a unique analytical tool to determine both the thickness and structure of this poorly structured oxide during process development. A single wavelength ellipsometer monitoring scheme for both the appearance as well as the thickness of this inadvertent oxide layer is proposed for use in high-volume manufacturing.
Keywords: auger effect; annealing; ellipsometry; etching; metallic thin films; ohmic contacts; oxidation; titanium compounds